The Retroperitoneal Laparoscopic Renal Capsulectomy for Spontaneous Renal Subcapsular Fluid Collection: A Case-Series Report and Literature Review. Issue 21 (May 2016) - Zhu, Guodong; Wu, Dapeng; Wu, Kaijie; Song, Wenbin; Yang, Zhishang; Zhang, Yue; Zhang, Linlin; He, Dalin
Abstract : Abstract: Spontaneous renal subcapsular fluid collection may occur as a rare presentation of nephritic syndrome, and distension of the renal capsula and Gerota fascia due to massive fluid accumulation may cause pain. In addition, hypertension secondary to renal ischemia and activation of renin–angiotensin–aldosterone system may also occur. The objective of this study is to evaluate the surgical outcome of retroperitoneal laparoscopic renal capsulectomy for patients with this disease. We retrospectively analyzed the clinical data of 10 female patients with spontaneous renal subcapsular fluid collection, diagnosed with B ultrasound and enhanced computed tomography (CT) scan. Eight patients first underwent percutaneous renal subcapsular drainage, which seemed to be less effective, and then all patients underwent retroperitoneal laparoscopic renal capsulectomy. The volume of renal subcapsular fluid was documented, the fluid was examined by routine biochemical tests, and the excised renal capsules underwent pathological examination individually. The postoperative drainage time for each patient was documented, and follow-up was conducted 1, 3, 6, 12 months, and 2 years postoperatively. Retroperitoneal laparoscopic renal capsulectomy was successfully performed in all patients with no major complications. The average volume of renal subcapsular fluid was 436 milliliter (mL, 180–880 mL) in light yellow color, and the concentration of creatinine and urea nitrogen was quite similar to that of serum. The pathological findings revealed fibrous dysplasia of the renal capsule with chronic infiltration of inflammatory cells. The average drainage time was 11.5 days (5–30 days) postoperatively. All patients recovered 1 month after the operation and there were no recurrences with a mean follow-up period of 12 months (6–24 months). The reason for spontaneous renal subcapsular fluid collection is unknown, and the aim of treatment is mainly to alleviate symptoms. In our experience, retroperitoneal laparoscopic renal capsulectomy is an effective surgical treatment, especially for patients who were refractory to percutaneous renal subcapsular drainage, with no observed recurrence.